2005
DOI: 10.4081/ijas.2005.3s.119
|View full text |Cite
|
Sign up to set email alerts
|

Blood serum metabolites and meat quality in crossbred pigs experiencing different lairage time

Abstract: Pigs of two crosses: A (Duroc x Swedish Landrace) x Pietrain (n=24) and B (Swedish Landrace x Large White) x Pietrain (n=26) were used to investigate the effects of different lairage time (2 and 24 hours) on levels of stress and meat quality traits. No direct effect of lairage time on cortisol, lactate, electrolytes and meat quality parameters was observed. However, after long lairage time, pigs showed lower level of glucose and higher CK, AST and ALT activity. Crossbred B pigs exposed to short lairage time, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Preslaughter stress can also cause an increase in electrolyte concentrations, such as potassium, sodium, chloride, and calcium. This could negatively influence pork quality, which is shown by decreased muscle pH and lower water holding capacity, increasing the tendency towards PSE meat [7,22]. It has been reported that acute-phase proteins (APPs) are a useful tool in the assessment of animal welfare during the preslaughter period [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preslaughter stress can also cause an increase in electrolyte concentrations, such as potassium, sodium, chloride, and calcium. This could negatively influence pork quality, which is shown by decreased muscle pH and lower water holding capacity, increasing the tendency towards PSE meat [7,22]. It has been reported that acute-phase proteins (APPs) are a useful tool in the assessment of animal welfare during the preslaughter period [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Non-invasive, quick, accurate, and reliable on-site prediction of pork quality would facilitate the distribution of whole carcasses or carcass cuts for fresh pork, different processing sectors (dry-cured ham or sausage production), or for meat branding (e.g., premium meat, meat products with protection of geographical indications, protected designations of origin, and guaranteed traditional specialty) according to their intrinsic characteristics and potential quality value. To date, several studies [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] have investigated physiological stress biomarkers as potential predictors of meat quality, as indicated previously. However, the high inconsistency of results reflects the complexity of meat quality traits, which are affected by multiple interacting factors, including genetic background, breeding, environmental factors, preslaughter conditions, as well as slaughtering procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Blood samples from 30 buffaloes, equal number from either sex, from local abattoirs, were collected in heparinized and nonheparinized vials for harvesting plasma and serum, respectively. Sampling was done once, 2 h pre-slaughter (in the lairage), by jugular vein puncture and then again at slaughter (Salajpal et al, 2005). Total protein (TP) was estimated by biuret method, albumin by bromocresol green method, globulin by calculating the difference between total protein and albumin, glucose by Folin-Wu method, blood urea nitrogen (BUN) by diacetyl-monoxime method, creatinine by modified Folin-Wu method, cholesterol by Zaltki's method, total biliurubin by Malloy and Evelyn method, calcium (Ca) by Clark and Collip method, phosphorous (P) by Fiske and Subbarow method, magnesium (Mg) by Titan yellow method, chloride (Cl -) by the method of Schales and Schales, and sodium (Na) and potassium (K) were estimated by flame photometry (Hawks et al, 1954).…”
Section: Methodsmentioning
confidence: 99%
“…In pigs with long lairage signifi cantly higher blood lactate was observed compared to short lairage (Figure 3), suggesting that long lairage was as a more stressful procedure. Perez et al [33] did not fi nd signifi cant effect of lairage time on blood lactate, while Salajpal et al [30] determined that one group of pigs after short lairage showed higher blood lactate. Further, signifi cantly higher blood lactate was observed after rough handling compared to gentle handling.…”
mentioning
confidence: 99%
“…Increase in blood lactate concentration is often associated with preslaughter stress, so many factors affect blood lactate, such as equipment and construction of the slaughterhouse, transport [29], genotype [30], lairage time [31] and pig handling [29,32]. In pigs with long lairage signifi cantly higher blood lactate was observed compared to short lairage (Figure 3), suggesting that long lairage was as a more stressful procedure.…”
mentioning
confidence: 99%